Le récit intermédial comme dispositif traumatique dans The Rings of Saturn de W. G. Sebald - Anne-Laure Fortin-Tournès (Sillages Critiques)
In The Rings of Saturn, the reading process is experienced by the reader in terms of temporal variations. Sebald’s novel is indeed the combination of a narrative and of visual materials — photographs in particular — which sever the narrative thread and disrupt the linear temporality of reading by forming an apparatus which acts as a force of capture capable of performatively transforming our perception of time. The temporality which is thereby established is that of the intensive time of experience through which the gaping wounds of trauma may be explored. In its eruptive and disruptive power, Sebald’s anachronical intermedial narrative therefore troubles us, disquiets us and finally appears to us as the very embodiment of the traumatic symptom.